2013
DOI: 10.1063/1.4790588
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale structure of protamine/DNA complexes for gene delivery

Abstract: Understanding the internal packing of gene carriers is a key-factor to realize both gene protection during transport and de-complexation at the delivery site. Here, we investigate the structure of complexes formed by DNA fragments and protamine, applied in gene delivery. We found that complexes are charge- and size-tunable aggregates, depending on the protamine/DNA ratio, hundred nanometers in size. Their compactness and fractal structure depend on the length of the DNA fragments. Accordingly, on the local sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Protamines, responsible for sperm chromatin condensation, have been chosen for their precise amino acid composition and high charge density (21 over 30 amino acids are positively charged in salmon protamine). Soluble DNA-protamine complexes formed at low DNA and salt concentration as established in previous studies 26 27 28 remain stable for months. We focus here on the mechanisms involved in their formation and stability by using a combination of multiple experimental and simulation approaches.…”
supporting
confidence: 62%
“…Protamines, responsible for sperm chromatin condensation, have been chosen for their precise amino acid composition and high charge density (21 over 30 amino acids are positively charged in salmon protamine). Soluble DNA-protamine complexes formed at low DNA and salt concentration as established in previous studies 26 27 28 remain stable for months. We focus here on the mechanisms involved in their formation and stability by using a combination of multiple experimental and simulation approaches.…”
supporting
confidence: 62%
“…This value for the Porod exponent reveals a typical feature of long-range clustering in biological macromolecules 41 and suggested structures with sharp interfaces and a surface fractal dimension of D s = 6 -3.6 = 2.4. 41,42 An intense peak at q 0 = 1.12 nm -1 , followed by its second order at q 1 = 2.25 nm -1 , indicated a repeat distance of d = 2/q 0 = 5.6 nm which can be ascribed to the separation between layers in a lamellar structure containing DNA in the interstices. Since the diameter of double-stranded DNA without a counter ion solvation shell was around 2 nm, 4 lamellae formed upon complexation can be smaller than rod-like micelles formed by the lipopeptide.…”
Section: Structural Analysis Of Peptide Complexation With Short Dna Fmentioning
confidence: 97%
“…limits the complex to cross the cellular membrane (11). Therefore, there is absolutely essential to facilitate an electrostatic interaction between protamine and the negative charge on the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…In order to promote the transfection process, it is desired to facilitate the electrostatic interaction of the transfection reagent with the negative charge of DNA backbone and the cell membrane (11). Also, previous data has been shown that precondensation of DNA by an additional cationic charge improves its protection against degradation (12).…”
Section: Introductionmentioning
confidence: 99%